Oxidation characteristics of Ti3AlC2, Ti3SiC2 and Ti2AlC - Pang, Wei Kong; Oo, Zeya; Hanna, J; Low, It Meng (Woodhead Publishing Limited, 2012)
MAX phases display a unique combination of characteristics of both metals and ceramics, and unusual mechanical, electrical and thermal properties. In this chapter, the oxidation characteristics of Ti3AlC2, Ti3SiC2 and Ti2AlC over the temperature range 500-1400 °C were studied by synchrotron radiation diffraction, neutron diffraction, secondary-ion mass spectrometry (SIMS) and nuclear magnetic resonance (NMR) experiments, which provided elemental and phase compositional depth profiles over this range as well as evidence of glassy phase formation. Evidence for the outward diffusion of Al or Si during oxidation was shown for the first time by the complementary SIMS and NMR results, suggesting amorphous Al or Si at low temperature oxidation, which is vital for strong adherent oxide scales during oxidation. During oxidation, anatase formed at 500 °C, which transformed to rutile at 600 °C and was completed by 900 °C. The crystalline phase alpha-Al2O3 was detected at 900 °C in Ti3AlC2 or Ti2AlC. Tridymite and cristobalite were detected at 1000 and 1350 °C respectively in Ti3SiC2.